Phase I Study of Preoperative Chemoradiotherapy Using Gemcitabine Plus Nab-Paclitaxel for Patients Who Have Localized Pancreatic Ductal Adenocarcinoma With Contact or Invasion to Major Arteries. Issue 8 (September 2021) - Hayasaki, Aoi; Kishiwada, Masashi; Murata, Yasuhiro; Komatsubara, Haruna; Nakagawa, Yuki; Maeda, Koki; Shinkai, Toru; Noguchi, Daisuke; Gyoten, Kazuyuki; Fujii, Takehiro; Iizawa, Yusuke; Tanemura, Akihiro; et al.
Abstract : Objectives: This study aimed to assess the feasibility of preoperative chemoradiotherapy using gemcitabine plus nab-paclitaxel (GnP) and to determine the recommended dose (RD) of nab-paclitaxel for patients with localized pancreatic ductal adenocarcinoma (PDAC). Methods: The participants had localized PDAC with contact or invasion to major arteries. They received GnP on days 1, 15, 29, and 43. The dose of gemcitabine was fixed at 600 mg/m 2, whereas that of nab-paclitaxel was at 3 dose levels in accordance with a standard 3 + 3 dose escalation scheme. Three-dimensional radiotherapy was administered concurrently to a total dose of 50.4 Gy per 28 fractions. Results: The study cohort comprised 15 patients. Grade 3 or 4 neutropenia was observed in 4 (26.7%), leukopenia in 1 (6.7%), biliary infection in 2 (13.3%), appetite loss and nausea in 1 (6.7%), and anaphylaxis in 1 (6.7%). The RD was determined as level 2 (gemcitabine, 600 mg/m 2 ; nab-paclitaxel, 100 mg/m 2 ). Three patients underwent pancreatectomy after additional chemotherapy and achieved R0 resection. Conclusions: The RD of nab-paclitaxel in our chemoradiotherapy protocol using GnP was 100 mg/m 2 with gemcitabine 600 mg/m 2 and 3-dimensional conformal radiotherapy to a total dose of 50.4 Gy per 28 fractions for patients with localized PDAC.